Risk factors for the persistence of unruptured intracranial vertebral artery dissecting aneurysms treated with flow diverters - Jiangli Han; Xiaobo Li; Hao Niu; Long Lin; Aihua Liu; Ying Xia (Scientific Reports)
Abstract Flow diverters (FDs) have been employed in the treatment of unruptured intracranial vertebral artery dissecting aneurysms (IVADAs), yielding seemingly favorable outcomes. Despite FD treatment, aneurysm persistence (incomplete occlusion post-initial treatment) can occur in some patients, potentially leading to recurrent symptoms or complications. This study aims to explore the risk factors associated with the persistence of unruptured IVADAs that have undergone treatment with FDs. The study encompassed 77 unruptured IVADAs from 75 consecutive patients who received treatment with FDs. At a median follow-up of 13 months, 31.2% (24/77) of IVADAs exhibited persistence. Upon multivariate logistic regression analysis, significant pre-procedural stenosis adjacent to aneurysmal dilatation (odds ratio [OR] 17.02, 95% confidence interval [CI] 2.01–144.24, p = 0.009) and posterior inferior cerebellar artery involvement (OR 7.06, 95% CI 1.40–35.50, p = 0.018) were independently associated with aneurysm persistence; while follow-up duration (OR 0.91, 95% CI 0.84–0.97, p = 0.005) was adversely associated with aneurysm persistence. Significant pre-procedural stenosis adjacent to aneurysmal dilatation and posterior inferior cerebellar artery involvement could serve as independent risk factors contributing to the persistence of unruptured IVADAs after FD treatment. .